Method for capturing carbon dioxide by using nickel-iron slag and application thereof
Patent Information
- Application Number
- CN202611490621.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]针对现有技术中镍铁渣综合利用率低、大量堆存引发环境风险,以及传统CO2矿化工艺能耗高、反应条件苛刻等问题,本发明提供一种利用镍铁渣高效捕集二氧化碳的方法
(1)本发明以工业固废镍铁渣为原料,通过温和的碱激发活化与低温碳化工艺实现二氧化碳捕集,反应条件为常压常温,能耗显著低于传统高温高压矿化路线,工艺流程简洁、操作简便,具有良好的工业化应用前景;
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of industrial solid waste resource utilization and carbon capture technology, and in particular to a method and application for capturing carbon dioxide using nickel-iron slag. Background Technology
[0002] Mineral carbonation technology is considered one of the most promising end-of-pipe CO2 disposal methods because it can convert CO2 into thermodynamically stable carbonate minerals, achieving permanent geological carbon sequestration. The core of this technology lies in utilizing the carbonation reaction between basic silicate minerals and CO2 to generate stable carbonates, thereby achieving long-term carbon fixation.
[0003] Nickel-iron slag is rich in magnesium-based components, with forsterite (Mg2SiO4) being the main mineral present. Theoretically, it is a highly promising low-cost CO2 mineralization raw material. Compared with natural magnesium silicate minerals, using metallurgical solid wastes such as nickel-iron slag as carbonation raw materials has significant advantages such as wide availability, no mining required, and low cost. It can simultaneously realize the resource utilization of large-scale solid waste and the effective sequestration of CO2, achieving both environmental and economic benefits. However, the Mg2SiO4 mineral in nickel-iron slag has a dense structure and high chemical stability. The Mg-O and Si-O bonds in its crystal lattice have a large bonding energy, making it difficult to effectively dissociate under normal temperature and pressure and simple water leaching conditions. The dissolution efficiency of magnesium ions is extremely low, resulting in a direct carbonation reaction conversion rate that is far from meeting industrial requirements.
[0004] To address this technological bottleneck, existing research has attempted to improve reactivity through activation pretreatment methods such as high-temperature roasting, acid leaching, or mechanical ball milling. For example, Chinese invention patent application CN114716269A discloses a method for producing citrate-soluble fertilizer by roasting and detoxifying / activating asbestos tailings or nickel-iron slag. This method combines magnetic separation and high-temperature roasting with chlorination roasting, solving the utilization problems of heavy metals and silicon-magnesium elements in asbestos tailings and nickel-iron slag, achieving full resource utilization of these materials and increasing the added value of the products. Chinese invention patent CN115650624B discloses a metal smelting waste slag-derived material and its preparation method and application. Through a mechanochemical reaction in a carbon dioxide and water vapor atmosphere, calcium oxide and magnesium oxide in metal smelting waste slag are transformed into calcium carbonate whiskers, forming a high-strength, high-toughness two-dimensional structure. This solves the problems of low hydration activity and insufficient volume stability of smelting waste slag, achieving efficient cement substitution. However, the above methods generally suffer from problems such as high energy consumption, severe equipment corrosion, complex processes, or the generation of secondary waste liquid, making it difficult to balance economic efficiency and carbon sequestration efficiency.
[0005] Therefore, there is an urgent need in this field to develop a low-energy-consumption and high-efficiency integrated process for the activation and carbonization of nickel-iron slag. This process involves using mild chemical activation to reconstruct the lattice of the stable magnesium olivine phase in the slag, thereby releasing the active magnesium components and achieving efficient capture and permanent mineralization and storage of CO2 under hydrothermal carbonization conditions. Summary of the Invention
[0006] To address the problems of low comprehensive utilization rate of nickel-iron slag, environmental risks caused by large-scale stockpiling, and high energy consumption and harsh reaction conditions in traditional CO2 mineralization processes, this invention provides a method for efficiently capturing carbon dioxide using nickel-iron slag. This method uses the magnesia olivine (Mg2SiO4) phase in nickel-iron slag as the active carbon-fixing component. Through sodium hydroxide solid alkali activation, the stable magnesium silicate lattice in the nickel-iron slag is selectively destroyed and reconstructed under mild heat treatment conditions, transforming the magnesium component, originally existing in stable silicate form, into magnesium oxide (MgO) phase with high carbonation reactivity. Subsequently, the activated material is contacted with CO2-containing gas in an aqueous system, where a carbonation reaction occurs efficiently under ambient temperature and pressure, converting CO2 into thermodynamically stable magnesite (MgCO3), thereby achieving permanent CO2 mineralization and sequestration. This method integrates the processes of "nickel-iron slag alkali activation - release of active magnesium components - CO2 mineralization and fixation at ambient temperature and pressure."
[0007] The first aspect of this invention provides a method for capturing carbon dioxide using nickel-iron slag, comprising the following steps: (1) The original nickel-iron slag is crushed, ground and sieved to obtain nickel-iron slag powder; the obtained nickel-iron slag powder is mixed with sodium hydroxide, pressed into briquettes, and melted under an inert atmosphere to obtain an alkaline activated sample; (2) Cool, grind, wash with water until neutral, and dry the alkaline activated sample obtained in step (1) to obtain active MgO; mix the obtained active MgO with water to form a slurry; (3) Under normal pressure, CO2 gas is continuously introduced into the slurry obtained in step (2), and carbonization reaction is carried out under constant temperature stirring conditions; (4) After the carbonization reaction is completed, solid-liquid separation and drying are performed to obtain MgCO3 product; Optionally, in step (1), the mass ratio of the nickel-iron slag powder to sodium hydroxide is 1:(1.6~2). Optionally, in step (2), the solid-liquid ratio of the active MgO to water is 1 g: (5~25) mL.
[0008] Optionally, in step (3), the flow rate of CO2 gas introduced is 100~1000 mL / min.
[0009] Optionally, in step (1), the temperature of the melting treatment is 400~600℃.
[0010] Optionally, in step (3), the carbonization reaction temperature is 20~80℃ and the carbonization reaction time is 1~4h.
[0011] Optionally, in step (3), the temperature is increased to the carbonization reaction temperature at a heating rate of 5~15℃ / min.
[0012] Optionally, in step (3), the stirring speed is 200~800 rpm.
[0013] Optionally, in step (4), the drying temperature is 70~100℃.
[0014] Optionally, the CO2 capture efficiency of the method is above 2%.
[0015] Optionally, the MgCO3 product obtained by the method has a mass fraction of 4% or more.
[0016] A second aspect of the present invention provides an application of the method for capturing carbon dioxide using nickel-iron slag as described above, the method being applied to the resource utilization of industrial solid waste or the mineral sequestration of CO2.
[0017] Beneficial effects: This invention provides a method and application for capturing carbon dioxide using nickel-iron slag, which has the following advantages: (1) This invention uses industrial solid waste nickel-iron slag as raw material and achieves carbon dioxide capture through mild alkali activation and low-temperature carbonization process. The reaction conditions are normal pressure and temperature, and the energy consumption is significantly lower than the traditional high temperature and high pressure mineralization route. The process is simple and easy to operate, and has good prospects for industrial application. (2) This invention transforms the originally non-carbonization reactive bound magnesium component into highly reactive porous magnesium oxide by directional alkaline activation of the inert magnesium olivine phase in nickel-iron slag, thereby significantly improving its ability to mineralize and capture CO2. (3) By controlling the mass ratio of nickel-iron slag powder to sodium hydroxide within the preferred range, this invention provides sufficient alkali supply for the full deconstruction of magnesium olivine lattice, ensuring a high yield of active MgO, while avoiding material melting and agglomeration and side reaction problems caused by excessive alkali, thus achieving a good balance between activation efficiency and process economy. (4) By controlling the solid-liquid ratio of active MgO to water within an optimal range, this invention ensures that the carbonization reaction system has both good slurry fluidity and suitable ion concentration, thus guaranteeing the gas-liquid-solid three-phase mass transfer efficiency of CO2 and maintaining the MgO concentration within a suitable range. 2+ With CO3 2-The effective collision frequency between them allows the carbonization reaction to be completed efficiently at room temperature and pressure; (5) This invention simultaneously realizes the high-value-added resource utilization of nickel-iron slag and the permanent mineral sequestration of carbon dioxide. This method not only disposes of industrial waste slag, but also transforms it into stable carbonate minerals with potential application value (such as building material fillers, soil conditioners, etc.), truly realizing the circular economy goal of "treating waste with waste and turning waste into treasure". Detailed Implementation
[0018] The first aspect of this invention provides a method for capturing carbon dioxide using nickel-iron slag, comprising the following steps: (1) The original nickel-iron slag is crushed, ground and sieved to obtain nickel-iron slag powder; the obtained nickel-iron slag powder is mixed with sodium hydroxide, pressed into briquettes, and melted under an inert atmosphere to obtain an alkaline activated sample; (2) Cool, grind, wash with water until neutral, and dry the alkaline activated sample obtained in step (1) to obtain active MgO; mix the obtained active MgO with water to form a slurry; (3) Under normal pressure, CO2 gas is continuously introduced into the slurry obtained in step (2), and carbonization reaction is carried out under constant temperature stirring conditions; (4) After the carbonization reaction is completed, solid-liquid separation and drying are carried out to obtain MgCO3 product.
[0019] The nickel-iron slag described in this invention refers to industrial solid waste discharged during the production of nickel-iron alloys. Its main chemical composition includes SiO2, MgO, FeO, Al2O3, CaO, etc., with the main mineral phases being forsterite (Mg2SiO4), firite (Fe2SiO4), and a portion of silicate glass phase. Forsterite (Mg2SiO4) is the main mineral containing MgO in the nickel-iron slag and is also the key calcium / magnesium source component for carbonization and carbon dioxide capture in this invention. The MgO and SiO2 in this mineral phase are combined in a stable silicate form, which is difficult to react directly with CO2 under normal temperature and pressure. Therefore, chemical activation methods are needed to disrupt its stable crystal structure, allowing the MgO to react with the SiO2. 2+ Only when MgO is released can it combine with CO2 in the subsequent carbonization step to form magnesium carbonate (MgCO3), thereby achieving efficient CO2 capture.
[0020] This invention is based on a stepwise reaction mechanism of "alkali-induced lattice reconstruction - release of active magnesium - room-temperature mineralization and carbon fixation". Its carbon fixation process mainly includes the following chemical reactions (1) to (4): Mg2SiO4+2NaOH→2MgO+Na2SiO3+H2O formula (1) MgO + H₂O → Mg(OH)₂ (Equation 2) Mg(OH)2 Mg2+ +2OH - Equation (3) Mg 2+ +CO3 2- +3H2O→MgCO3·H2O formula (4) Formula (1) is the core activation step of this invention. Magnesia olivine (Mg2SiO4) in nickel-iron slag has a stable silicate lattice structure, in which Mg... 2+ Surrounded by silicon-oxygen tetrahedra, Mg2SiO4 exhibits high chemical stability and is difficult to react directly with CO2 at room temperature and pressure. This invention employs a mixture of solid sodium hydroxide and nickel-iron slag powder, followed by heat treatment. The strong alkalinity of NaOH disrupts the Si-O bonds in Mg2SiO4 under high-temperature conditions, causing the crystal structure of forsterite to decompose. The magnesium component is released as active MgO, while the silicon component exists as soluble sodium metasilicate (Na2SiO3). This sodium metasilicate can be removed during subsequent water washing, thus achieving effective separation of the magnesium and silicon components. It should be noted that NaOH is not a catalyst in this step but rather participates in the decomposition reaction of forsterite as a reactant. With the consumption of NaOH and the formation of Na2SiO3, the alkaline environment of the system provides the chemical driving force for the continued decomposition of Mg2SiO4.
[0021] Furthermore, equations (2) and (3) represent the transformation process of the activated product in the aqueous phase. The activated MgO obtained via equation (1) first undergoes a hydration reaction upon entering the aqueous system, as shown in equation (2), to generate magnesium hydroxide. Magnesium hydroxide is a slightly soluble substance and exists in a dissociation equilibrium in aqueous solution, as shown in equation (3), slowly dissociating and releasing Mg from the aqueous phase. 2+ Together with hydroxide ions, it provides a magnesium ion source for subsequent carbonization and carbon fixation reactions.
[0022] Furthermore, equation (4) represents the carbonation fixation step of this invention. The active MgO generated after alkali activation exhibits certain carbonation reactivity in the aqueous system, capable of reacting with CO2 dissolved in water to undergo carbonation, generating thermodynamically stable magnesite (MgCO3). In this step, CO2 first dissolves in water to form carbonic acid (H2CO3), and the carbonic acid dissociates to generate H... + With HCO3 - / CO3 2- Active MgO hydrates in the aqueous phase to form Mg(OH)2 and slowly releases Mg. 2+ Mg 2+ With CO3 2-The reaction produces MgCO3 precipitate. This reaction is exothermic and can proceed spontaneously under normal temperature and pressure conditions without the need for external high temperature and pressure. The generated MgCO3 has extremely high thermodynamic stability, which can achieve permanent mineralization and sequestration of CO2, avoiding the risk of secondary CO2 leakage that exists in traditional geological or biological sequestration methods.
[0023] Optionally, in step (1), a 50-400 mesh sieve is used for sieving; the mesh sizes can be listed as 50 mesh, 100 mesh, 150 mesh, 200 mesh, 250 mesh, 300 mesh, 350 mesh, 400 mesh, etc.; the most suitable mesh size is 200 mesh.
[0024] Optionally, in step (1), the mass ratio of nickel-iron slag powder to sodium hydroxide is 1:(1.6~2); it can be listed as 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, etc.
[0025] Optionally, in step (1), the sodium hydroxide is ground into powder before being mixed with the nickel-iron slag powder.
[0026] Optionally, in step (1), the pressure of the pressure block is 10~30MPa; it can be listed as 10MPa, 15MPa, 20MPa, 25MPa, 30MPa, etc.
[0027] Optionally, in step (1), after pressing, a blank with a diameter of 10~30mm and a height of 10~50mm is obtained.
[0028] Optionally, in step (1), the inert atmosphere can be listed as nitrogen, argon, etc.; it can also be nitrogen.
[0029] Optionally, in step (1), the melting temperature is 400~600℃ and the melting time is 2~6h; the melting temperature can be listed as 400℃, 450℃, 500℃, 550℃, 600℃, etc.; further optionally, the melting temperature is 500℃.
[0030] This invention uses sodium hydroxide (NaOH) as a chemical activator, its core function being to induce alkali-induced destructive effects on the chemically stable forsterite (Mg2SiO4) lattice in nickel-iron slag. Forsterite is an island silicate mineral, its crystal structure consisting of isolated [SiO4] crystals. 4- Tetrahedrons and Mg² filling the interstices of the tetrahedrons + Composed of strong ionic and covalent bonds, the Si-O bond has high bond energy and large lattice energy, making it difficult to spontaneously break in normal temperature, normal pressure, and neutral aqueous solution environments. Therefore, magnesium olivine exhibits extremely strong chemical inertness.
[0031] When NaOH is mixed with nickel-iron slag and subjected to appropriate heat treatment, the OH groups released by the NaOH dissociate under high temperature conditions - It possesses extremely strong nucleophilic attack capabilities, able to attack the Si-O bonds in the Si-O-Mg bonding units of forsterite, causing [SiO4] to... 4- Tetrahedral depolymerization occurs. Simultaneously, Mg... 2+ Detached from the olivine lattice, reacting with OH - They combine to form an active magnesium oxide (MgO) phase; while the depolymerized silicate ions react with Na+. + Soluble sodium metasilicate (Na₂SiO₃) is formed through this process. Essentially, NaOH breaks the Si-O bonds of Mg₂SiO₄, releasing the previously non-carbonatized magnesium components from the slag and transforming them into an active magnesium source capable of reacting with CO₂. During this process, NaOH is consumed as a reactant. With the continuous deconstruction of the forsterite lattice and the continuous generation of Na₂SiO₃, the alkaline microenvironment of the system is maintained, providing a sustained chemical driving force for the deep decomposition of forsterite.
[0032] The extent of the activation reaction described above is closely related to the amount of NaOH supplied. In this invention, NaOH participates directly in the reaction as a reactant in the disintegration of the forsterite crystal lattice, and also acts as a molten medium to improve the solid-phase reaction interface during heat treatment—its amount directly determines the completeness of the activation reaction and the yield of active MgO. When the amount of NaOH is too low (e.g., below the stoichiometric ratio required for the complete decomposition of forsterite), the OH- in the system... - Insufficient NaOH concentration leads to insufficient lattice deconstruction of forsterite, resulting in some forsterite particles undergoing only slight surface alteration while maintaining their internal lattice integrity. This results in the actual amount of active MgO generated being far lower than the theoretically releaseable amount. Consequently, the magnesium component in the nickel-iron slag is not fully utilized, and unreacted forsterite remains in the activation products. The magnesium component encapsulated within cannot participate in subsequent carbonization steps, wasting magnesium resources and diluting the active component due to the residual inert forsterite, thus reducing the overall conversion efficiency of the carbonization reaction. While excessive NaOH ensures sufficient activation of forsterite, it also forms a large amount of molten phase at high temperatures, exacerbating particle adhesion and agglomeration. This increases the burden on subsequent grinding and washing processes, and requires more deionized water during washing, increasing wastewater generation and treatment costs. More importantly, excessive NaOH at high temperatures may further react with the generated active MgO to produce byproducts such as metamagnesates (Na2MgO2, etc.), further reducing the yield of effective active magnesium components. Through experimental investigation, this invention has found that when the mass ratio of nickel-iron slag powder to NaOH is controlled within the range of 1:(1.6~2), sufficient OH groups can be provided for the full activation of magnesium olivine.- The optimal alkali ratio ensures effective disassembly of the magnesium olivine lattice and high yield of active MgO, while avoiding material agglomeration and side reactions caused by excessive alkali. Within this optimal ratio range, the activation rate of magnesium olivine in nickel-iron slag and subsequent carbonization conversion rate both reach ideal levels, while also achieving process economy.
[0033] Optionally, in step (2), the solid-liquid ratio of the active MgO to water is 1g:(5~25)mL; examples include 1g:5mL, 1g:10mL, 1g:15mL, 1g:20mL, 1g:25mL, etc.
[0034] Optionally, in step (2), the drying temperature is 80~100℃; it can be listed as 80℃, 85℃, 90℃, 95℃, 100℃, etc.; the drying time is 6-20h; it can be listed as 6h, 7h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, etc.
[0035] In this invention, the solid-liquid ratio of active MgO to water is one of the key parameters affecting carbonization efficiency. In the actual reaction process, water plays a triple role as reactant, solvent, and mass transfer medium: MgO must first be hydrated to Mg(OH)₂ before carbonization can occur, and simultaneously, the dissolution of CO₂ and the reaction with MgO... 2+ The migration of Mg depends on a sufficient liquid phase environment. When water is insufficient, the slurry becomes viscous, CO2 diffusion is hindered, gas-liquid-solid three-phase mass transfer is limited, and reaction kinetics decrease significantly; when water is excessive, Mg... 2+ Excessively diluted, with CO3 2- The effective collision probability decreases, and the reaction driving force weakens. Experiments have verified that when the solid-liquid ratio is controlled within the range of 1 g:(5~25) mL, the system possesses both good fluidity and suitable ion concentration, allowing the carbonization reaction to be efficiently completed at room temperature and pressure.
[0036] Optionally, in step (3), the flow rate of CO2 gas introduced is 100~1000 mL / min; it can be listed as 100 mL / min, 150 mL / min, 200 mL / min, 300 mL / min, 400 mL / min, 500 mL / min, 600 mL / min, 700 mL / min, 800 mL / min, 900 mL / min, 1000 mL / min, etc.; it can be further selected as 500 mL / min.
[0037] Optionally, in step (3), the carbonization reaction temperature is 20~80℃ and the carbonization reaction time is 1~4h; the carbonization temperature can be listed as 20℃, 30℃, 40℃, 50℃, 60℃, 70℃, 80℃, etc.; the carbonization reaction time can be listed as 1h, 2h, 3h, 4h, etc.; further optionally, the carbonization reaction temperature is 40~60℃.
[0038] Optionally, in step (3), the temperature is increased to the carbonization reaction temperature at a heating rate of 5~15℃ / min; examples include 5℃ / min, 8℃ / min, 10℃ / min, 12℃ / min, 15℃ / min, etc.
[0039] Optionally, in step (3), the stirring speed is 200~800 rpm; it can be listed as 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, etc.; it can be further selected as 300 rpm.
[0040] In some embodiments, a ball mill can be used for pulverization in step (1), and a mortar and pestle can be used for grinding; the melting process in step (1) can be carried out in a tube furnace; and the carbonization reaction in step (3) can be carried out in a water bath. This invention does not impose any particular limitation on the specific equipment used in the above operations, as long as it can achieve the purpose of each step; those skilled in the art can make conventional substitutions or equivalent replacements for the above equipment according to the actual production scale and laboratory conditions, without affecting the implementation effect of the technical solution of this invention.
[0041] Optionally, in step (4), the solid-liquid separation method is filtration.
[0042] Optionally, in step (4), the drying temperature is 70~100℃, and the product is dried to constant weight; the drying temperature can be listed as 70℃, 80℃, 90℃, 100℃, etc.
[0043] Optionally, the CO2 capture efficiency of the method is 2% or higher; more preferably, it is 8% or higher.
[0044] Optionally, the MgCO3 product obtained by the method has a mass fraction of 4% or more; more preferably, it has a mass fraction of 10% or more.
[0045] A second aspect of the present invention provides an application of the method for capturing carbon dioxide using nickel-iron slag as described above, the method being applied to the resource utilization of industrial solid waste or the mineral sequestration of CO2.
[0046] This invention utilizes nickel-iron slag as raw material and employs an integrated process of alkali activation and ambient temperature mineralization to simultaneously achieve resource utilization of bulk industrial solid waste and permanent mineral sequestration of CO2. This method can be applied to the on-site treatment of nickel-iron slag generated by nickel-iron smelting enterprises, and can also be extended to the carbonization disposal of other metallurgical waste slags rich in calcium and magnesium components.
[0047] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0048] The original nickel-iron slag in the following implementation case comes from Inner Mongolia. The main mineral phases are magnesium olivine, fir olivine and silicate glass phase; the sodium hydroxide used is analytical grade; the high-purity nitrogen used is 4N purity grade; and the high-purity CO2 used is 99.999% pure.
[0049] Example 1 This embodiment provides a method for capturing carbon dioxide using nickel-iron slag, including the following steps: (1) The original nickel-iron slag was crushed, ground and passed through a 200-mesh sieve using a ball mill to obtain nickel-iron slag powder; the obtained nickel-iron slag powder was mixed with sodium hydroxide solid (already ground into powder) at a mass ratio of 1:2, and placed in a mold and pressed with a pressure of 20 MPa to obtain a cylindrical blank with a diameter of 20 mm and a height of 30 mm; the blank was placed in a crucible and transferred to a high-temperature tube furnace, and high-purity nitrogen was introduced as an inert atmosphere (gas flow rate 150 mL / min), and the temperature was raised from room temperature to 500℃ at a heating rate of 10℃ / min for 4 h to obtain an alkaline activated sample; (2) Cool the alkaline-activated sample obtained in step (1) to room temperature naturally, grind it, wash it with deionized water until neutral, filter and collect the solid product after washing, dry it in an oven at 100°C for 12 hours to obtain active MgO; mix the obtained active MgO with deionized water at a solid-liquid ratio of 1g:10mL to form a slurry; place the slurry in a three-necked flask reactor equipped with a gas distributor and a stirring device; (3) Under normal pressure, the reactor water bath is heated to 40°C and kept constant. High-purity CO2 gas (gas flow rate 500 mL / min) is continuously introduced into the reactor, and stirring is started at 300 rpm. The carbonization reaction is carried out for 4 hours. (4) After the carbonization reaction is completed, the material is filtered and washed, and the solid product is dried at 100°C to constant weight to obtain MgCO3 product.
[0050] Example 2 This embodiment provides a method for capturing carbon dioxide using nickel-iron slag. The specific implementation method is the same as in embodiment 1. The difference is that in step (2), active MgO and deionized water are mixed at a solid-liquid ratio of 1g:5mL.
[0051] Example 3 This embodiment provides a method for capturing carbon dioxide using nickel-iron slag. The specific implementation method is the same as in embodiment 1; the difference is that the carbonization reaction temperature in step (3) is 60°C.
[0052] Comparative Example 1 This comparative example provides a method for capturing carbon dioxide using nickel-iron slag, including the following steps: (1) The original nickel-iron slag was crushed, ground and passed through a 200-mesh sieve using a ball mill to obtain nickel-iron slag powder; (2) Mix the nickel-iron slag powder obtained in step (1) with deionized water at a solid-liquid ratio of 1g:10mL to form a slurry; place the slurry in a three-necked flask reactor equipped with a gas distributor and a stirring device; (3) Under normal pressure, the reactor water bath is heated to 40°C and kept constant. High-purity CO2 gas (gas flow rate 500 mL / min) is continuously introduced into the reactor, and stirring is started at 300 rpm. The carbonization reaction is carried out for 4 hours. (4) After the carbonization reaction is completed, the material is filtered and washed, and the solid product is dried at 100°C to constant weight.
[0053] Comparative Example 2 This comparative example provides a method for capturing carbon dioxide using nickel-iron slag. The specific implementation method is the same as in Example 1. The difference is that in step (1), the mass ratio of nickel-iron slag powder to sodium hydroxide is 1:1.5. During operation, the amount of nickel-iron slag powder is kept constant, and the amount of sodium hydroxide powder added is adjusted.
[0054] Comparative Example 3 This comparative example provides a method for capturing carbon dioxide using nickel-iron slag. The specific implementation method is the same as in Example 1. The difference is that in step (2), the solid-liquid ratio of active MgO to deionized water is 1g:30mL. During operation, the amount of active MgO is kept constant, and the amount of deionized water added is adjusted.
[0055] Performance testing The solid products dried to constant weight in step (4) of each embodiment and comparative example were subjected to thermogravimetric analysis (TGA) to evaluate the CO2 capture performance of the method of the present invention. The test conditions were: under a nitrogen atmosphere, the heating range was from room temperature to 1000°C, and the heating rate was 10°C / min. During the thermogravimetric analysis, magnesium carbonate (MgCO3) in the product underwent thermal decomposition in the temperature range of 350~550°C, releasing CO2 and generating magnesium oxide (MgO), accompanied by obvious weight loss steps; based on the weight loss rate of this weight loss step in the thermogravimetric curve, the content of MgCO3 in the product and the CO2 capture efficiency were calculated; the calculation formula is as follows, and the results are recorded in Table 1.
[0056] MgCO3 mass fraction = (mass of MgCO3 in the product / total mass of solid product after carbon fixation) × 100%; CO2 capture efficiency = (mass of MgCO3 in the product / mass of active MgO before carbon fixation) × 100%.
[0057] Table 1
[0058] Table 1 shows that Examples 1-3 all achieved effective CO2 capture and magnesium carbonate mineralization. Example 1 (solid-liquid ratio 1:10, carbonization temperature 40℃) showed the best carbon fixation effect with a CO2 capture efficiency of 11.59% and a MgCO3 mass fraction of 19.89%. Examples 2 (solid-liquid ratio 1:5) and Example 3 (carbonization temperature 60℃) also achieved different degrees of carbonization conversion, with capture efficiencies of 9.36% and 2.38%, and MgCO3 mass fractions of 16.40% and 4.46%, respectively. Comparative Examples 1-3 did not detect magnesium carbonate formation (capture efficiency and MgCO3 mass fraction were both 0%): Comparative Example 1 did not undergo an alkaline activation step, and the magnesium olivine lattice in the nickel-iron slag remained intact. 2+ The MgO could not be dissolved to participate in the carbonization reaction; in Comparative Example 2, the mass ratio of NaOH to nickel-iron slag was only 1:1.5, indicating insufficient alkali supply, which could not drive the full conversion of magnesium olivine to active MgO; in Comparative Example 3, the solid-liquid ratio was increased to 1:30, and the excess water diluted the MgO in the reaction system. 2+ With CO3 2- Concentration leads to the loss of the driving force for the carbonization reaction. The above comparison shows that by controlling the amount of alkali, the solid-liquid ratio, and the carbonization temperature within the preferred range, the present invention can effectively achieve the directional conversion of inert magnesium components in nickel-iron slag to active MgO and the efficient mineralization and capture of CO2; it reflects that the carbonization conditions need to be controlled within a reasonable range. When the conditions are insufficient, the reaction cannot be effectively started, and when they are excessive, the carbonization process is inhibited because the active sites are covered or deactivated. Deviation from this range will lead to a significant decrease in the carbon fixation effect.
[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for capturing carbon dioxide using nickel-iron slag, characterized in that, Includes the following steps: (1) The original nickel-iron slag is crushed, ground and sieved to obtain nickel-iron slag powder; the obtained nickel-iron slag powder is mixed with sodium hydroxide, pressed into briquettes, and melted under an inert atmosphere to obtain an alkaline activated sample; (2) Cool, grind, wash with water until neutral, and dry the alkaline activated sample obtained in step (1) to obtain active MgO; mix the obtained active MgO with water to form a slurry; (3) Under normal pressure, CO2 gas is continuously introduced into the slurry obtained in step (2), and carbonization reaction is carried out under constant temperature stirring conditions; (4) After the carbonization reaction is completed, solid-liquid separation and drying are performed to obtain MgCO3 product; In step (1), the mass ratio of the nickel-iron slag powder to sodium hydroxide is 1:(1.6~2). In step (2), the solid-liquid ratio of the active MgO to water is 1 g: (5~25) mL.
2. The method for capturing carbon dioxide using nickel-iron slag according to claim 1, characterized in that, In step (3), the flow rate of CO2 gas is 100~1000mL / min.
3. The method for capturing carbon dioxide using nickel-iron slag according to claim 1, characterized in that, In step (1), the melting temperature is 400~600℃.
4. The method for capturing carbon dioxide using nickel-iron slag according to claim 1, characterized in that, In step (3), the carbonization reaction temperature is 20~80℃ and the carbonization reaction time is 1~4h.
5. The method for capturing carbon dioxide using nickel-iron slag according to claim 4, characterized in that, In step (3), the temperature is increased to the carbonization reaction temperature at a heating rate of 5~15℃ / min.
6. The method for capturing carbon dioxide using nickel-iron slag according to claim 4, characterized in that, In step (3), the stirring speed is 200~800 rpm.
7. The method for capturing carbon dioxide using nickel-iron slag according to claim 1, characterized in that, In step (4), the drying temperature is 70~100℃.
8. The method for capturing carbon dioxide using nickel-iron slag according to claim 1, characterized in that, The CO2 capture efficiency of the method is above 2%.
9. The method for capturing carbon dioxide using nickel-iron slag according to claim 1, characterized in that, The MgCO3 product obtained by the method has a mass fraction of 4% or more.
10. An application of the method for capturing carbon dioxide using nickel-iron slag according to any one of claims 1 to 9, characterized in that, The method is applied to the resource recovery of industrial solid waste or the mineral sequestration of CO2.
Citation Information
Patent Citations
Method for preparing citrate-soluble fertilizer by roasting detoxification / activation of asbestos tailings or ferronickel slag
CN114716269A
A metal smelting waste slag derivative material, its preparation method and application
CN115650624B